Digitalization: A way forward for Filipino MSMEs during the COVID-19 pandemic - Mia, Ian Benedict R. (Animo Repository, 2021)
This article focuses on MSMEs that tried to weather the crisis and those that found innovative means to survive. We discuss the following: (1) the adjustments or innovations that MSMEs have done during the pandemic; (2) what the government has done to support or complement the changes being undertaken by MSMEs; and (3) a call to action meant to address the current survival – and eventually thriving – of MSMEs through digitalization and the rapid adoption of digital technologies.